Unethical Conduct as a Precursor to Ecological Crisis in Hosea and its Relevance to Rivers State, Nigeria (2014)
The book of Hosea, popular for its marital metaphor, presents a link between unethical deeds and ecological crises in ancient Israel. However, existing studies on the book have focused mostly on its nuptial imagery with less emphasis on the ecological consequences generated by unethical deeds in Israel of the period, which could be relevant to understanding the ecological problems in selected communities in contemporary Rivers State. This study, therefore, interpreted the Book of Hosea from an ecological standpoint with a view to establishing the consequences of unethical deeds brought on ancient Israel’s land, air, and water, and the relevance of these for understanding the environmental challenges in selected communities in Rivers State. The study adopted Habel’s ecological hermeneutics, which stresses that human deeds have ecological consequences. The Historical-Grammatical Method was utilised as exegetical platform to interpret the purposively selected text of Hosea 4:1-3. Two sets of questionnaire were administered: 583 copies to purposively sampled residents in Andoni, Ahoada-East, Etche, Khana, Ogba/Egbema/Ndoni and Port-Harcourt local government areas of Rivers State, which are highly vulnerable to environmental degradation, and 26 copies to Community Liaison Officers (CLOs) of Saipem/Agip, Total/Elf, Shell and Chevron. Media reports were consulted, and observations were made. Data were subjected to exegetical analysis and percentage scores. Hosea 4:1-2 outlined dysfunctional community relationships (we’en-chesed) manifested in destructive activities (pārats), blood-bath (rātsach), and stealing of humans/natural resources (gānab') as prevailing human misdeeds with environmental consequences in ancient Israel. Similarly in Rivers State, dysfunctional community relationships underpinned by pipeline vandalisation, oil spillage, oil theft, indiscriminate gas flaring and unethical use of chemicals and explosive exemplified unethical behaviours with environmental consequences. These were attested to by 89.4% of Residents and 88.5% of the CLOs. Hosea 4:3 echoed the attendant environmental consequences of such moral decadence: on land, human beings and beasts were adversely affected by man-induced drought; birds either migrated or became extinct as a result of atmospheric imbalance; in water, fish migrated or became extinct owing to excessive fishing motivated by greed. Equally, in Rivers State, community youths engaged in pipeline vandalisation while oil companies also engaged in oil spillage and dumping of high level hydrocarbon pollutants on the ground, thereby preventing the growth of vegetation, animal and human populations. This violation of ethics of environmental stewardship was affirmed by 80.4% of the residents, 73.1% of the CLOs and the media report of August 22, 2011 on United Nations Environmental Programme. There was bird mortality arising from indiscriminate gas flaring by oil companies. Community residents from fresh water zone applied chemicals while those of saline water zone used explosives as fishing techniques. This results in non-selective mortal damage, which leaves water sources stinking after two days. This was confirmed by 84.9% of community residents. Unethical deeds, which account for ecological disasters in the land, air and water in Hosea and selected communities in Rivers State, resulted from the violation of ethics of environmental stewardship. Therefore, practical adherence to moral tenets espoused in Hosea is imperative for environmental remediation in Rivers State